Developing the Arabic Vocabulary Test Material from Cognitive and Skill Domain Perspective/ تطوير مادة اختبار مفردات اللغة العربية على ضوء المجال المعرفي والمهاري - jumatiah Jumatiah; Ibrahim Helalsah (UIN ANTASARI, 2021)
Test is an important part in teaching and learning process. There are no schools and universities without tests and there is no alternative test to evaluate students objectively. The purpose of this study was to develop Arabic mufradat test material on cognitive and psychomotor aspects for grade 7 students at MTsN 1 Banjarmasin and MTsN 3 Banjarmasin, and to determine the validation of Arabic language experts and Arabic language evaluation experts on the products developed and the characteristics of the products developed.This type of research is research and development by Borg and Gall model modified by Sukmadina into 3 steps, namely 1) preliminary study, 2) model development, 3) model testing.The result is the steps in developing the material being developed, namely starting from the preliminary study stage then designing the material developed and then expert testing.The material developed is suitable for use and the results of the linguist's validation that the material developed is feasible with a value of 90%.